Evaluation of efficacy of bupivacaine and bupivacaine plus clonidine in transversus abdominis plane (TAP) block for postoperative analgesia: a prospective, randomized, double blind, comparative study - Mir, Tauqeer Anjum; Mir, Aabid Hussain; Gani, Tantry Tariq; Yousuf, Abida; Ahmad, Sheikh Irshad (International Journal of Research in Medical Sciences, 2017)
Background: Pain is the commonest symptom encountered postoperatively and hence multimodal analgesia is tried to overcome it. In this study, we have compared bupivacaine and bupivacaine plus clonidine in transversus abdominis plane (TAP) block for postoperative analgesia in patients undergoing lower abdominal surgeries under spinal anaesthesia. Methods: Sixty ASA I and II patients in the age range of 18-60 years undergoing various lower abdominal surgeries were randomly divided into two groups, who were operated after giving spinal block using 2.5 ml of 0.5% hyperbaric bupivacine and 25ug of fentanyl. At the end of surgical procedure tranversus abdominis plane (TAP) block was given by giving 25 ml of injection bupivacaine 0.25% in group I and 25 ml of 0.25% of bupivacaine with 1 ug.kg-1 of clonidine in group II. Quality of analgesia was assessed by visual analogue scale (VAS), categorical pain scoring system and frequency of rescue analgesia given and duration was assessed with the time at which first rescue analgesia was given. Side effects of clonidine such as sedation, bradycardia and hypotension were also noted. The hemodynamic parameters like heart rate (HR), systolic blood pressure (SBP) and diastolic blood pressure (DBP) were noted for both the groups. Results: Demographic characteristics like age, weight, sex, ASA class and type of surgeries were comparable in both groups. SBP, DBP and HR were less in group II than in group I and was statistically significant (p-value<0.05). The overall mean VAS score in group I was 3.03 ± 1.57 and group II was 1.72 ± 1.02 with p-value of 0.0005 and hence better quality of analgesia in group II. Categorical pain scoring system also showed statistically better scores in group II than group I. The duration of analgesia which was calculated by mean time for first rescue analgesia in group I was 6.38 ± 2.56 hours and group II was 14.23 ± 4.63 hours with a p-value of <0.0001 and the difference was statistically significant. The mean number of doses of rescue analgesia in group I for the first 24 hours was 1.37 ± 0.89 and in group II was 0.60 ± 0.62 with a p-value of 0.0003 and the difference was statistically significant. Group II patients showed more sedation scores than group I patients (p-value <0.05). None of the patients had any episode of bradycardia or hypotension. Conclusions: Addition of clonidine 1 ug.kg-1 to 25 ml of 0.25% bupivacaine compared to 25 ml of 0.25% bupivacaine alone in tranverse abdominis plane (TAP) block improves quality of analgesia, increases duration of postoperative analgesia and decreases postoperative analgesic requirements with minimal side effects.